The Increase of Efficiency in Robusta Green Coffee Bean Size Sorting Machine by Response Surface Methodology - Watcharapong Chanpaka; Naruebodee Srisang; Panya Dangwilailux; Thatchapol Chungcharoen (My University, 2020)
Abstract One of the essential processes for producing the green coffee bean with Robusta variety is size sorting process because it is able to add the value of green coffee bean. The excellent size sorting can be done by using the size sorting machine. In this study, the size sorting machine with revolved sieve which provided the good distribution of green coffee bean was used and the three factors such as sorting angle, revolved speed and feed rate were investigated using Response Surface Methodology (RSM) based on a Central Composite Design (CCD). The optimum conditions of size sorting efficiency were revolved speed of 8.35 rpm, sorting angle of 5.05 degree and feed rate of 26.59 kg/h. These provided the size sorting efficiency of 75.15% with high correlating coefficient (R2 = 97.65). This indicated that the data predicted with Response Surface Methodology was good agreement and adequacy of models.
Keywords: Sieve (category theory); Sieve analysis; Microbial Inactivation Methods